Adaptation of rammed earth to modern construction systems: Comparative study of thermal behavior under summer conditions. (1st August 2016) - Serrano, Susana; de Gracia, Alvaro; Cabeza, Luisa F.
Highlights: Rammed earth is adapted to modern requirements by reducing its thickness. Wooden insulation panels are placed in the outer face of rammed earth walls. Sustainable and conventional morphologies are thermally tested at real scale. Similar thermal response than in high embodied construction systems is achieved. Abstract: Buildings should be understood as a process that consumes energy in all their phases (design, construction, use and end-of-life) and, more specifically, the building envelope is clearly involved in all of them. For this reason, the International Energy Agency defines in its latest publication the improvement of building envelopes as one of the key points to reduce the energy consumption in buildings. In the present study, two sustainable construction systems based on rammed earth walls are adapted to modern requirements to be thermally tested and compared against three Mediterranean conventional systems under summer conditions. The experimentation was done by performing several experiments in free floating and controlled temperature conditions at real scale in five cubicle-shape buildings with inner dimensions 2.4 × 2.4 × 2.4 m. The purpose of this study is to demonstrate that more sustainable construction systems can be used instead of conventional ones, with higher embodied energy, and achieve similar thermal response. Results show that the reduction of rammed earth wall thickness strongly penalizes its thermal behavior. However, similar thermal response than conventional systems is reached when 6 cm of wooden insulation panels are added in the outer face of the cubicle-shape building.